PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI PADA UMKM SEKTOR JASA META PROPERTY BATAM - Calvin Wijaya; Dyfan Dyfan; Metta Metta; Yendi Yendi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The property business is one industry that enjoys high public demand in the contemporary day. For those of you who enjoy conducting business and making long-term investments, investing in real estate has turned into a passion. Property agents are currently making a sizable profit because of the current circumstances, which are progressively improving and trending in the commerce and real estate industries. However, property lenders who swarm to purchase homes at low prices and real estate brokers will also reap the rewards during periods of commerce and property booms and busts. The remedy suggested to Meta Property for this issue includes forecasting sales and marketing trends, researching rivals, conducting consumer surveys, researching and figuring out efficient ways to collect data, and requiring each real estate company to have a monthly target for unit sales. This meta property is extremely dependable and puts the demands of its customers first. It is processed fast and safely at home.